2009
DOI: 10.1227/01.neu.0000341517.65174.63
|View full text |Cite
|
Sign up to set email alerts
|

Surface Landmarks for the Junction Between the Transverse and Sigmoid Sinuses

Abstract: Because landmark data in the literature for externally identifying the transverse sigmoid sinus junction is variable, we have attempted to refine this location with the largest sample size to date. These data can assist surgeons to localize the external cranial projection of the area just inferior and medial to the junction between the transverse and sigmoid sinuses when image guidance devices are not available. This localization is important in creation of appropriate size for craniotomy/craniectomy during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 11 publications
0
56
0
Order By: Relevance
“…Unfortunately, the squamosal and parietomastoid sutures are often difficult to recognize during craniotomy, especially in older adults. Therefore, the SP and the intersection of the SCSS are not reliable landmarks for the ASTS [8,17]. The asterion is located at the junction of the parietomastoid, lambdoid and occipitomastoid sutures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the squamosal and parietomastoid sutures are often difficult to recognize during craniotomy, especially in older adults. Therefore, the SP and the intersection of the SCSS are not reliable landmarks for the ASTS [8,17]. The asterion is located at the junction of the parietomastoid, lambdoid and occipitomastoid sutures.…”
Section: Discussionmentioning
confidence: 99%
“…The transverse-sigmoid sinus junction was defined as the transitional zone where the transverse sinus ended by the vertical descending segment of the sigmoid sinus; the ASTS and IMTS were identified as the anterosuperior and inferomedial points of the junction, respectively [8,11] (Fig. 1).…”
Section: Definations Of the Asts Imts And Tmnmentioning
confidence: 99%
See 1 more Smart Citation
“…In the retrosigmoid keyhole approach, the transversesigmoid sinus junction should be fully exposed (3,23). In the past, neurosurgeons generally depend on the asterion and related sutures to determine the position of the transversesigmoid sinus junction (25,27,29). However, the transversesigmoid sinuses and junction sites of different people exhibit different anatomical characteristics (13,18,21,28,30), The most common complication in the retrosigmoid approach is CSF leakage (5), which is partly caused by the incomplete sealing of the opened mastoid air cell (10).…”
Section: █ Discussionmentioning
confidence: 99%
“…A vertical line is also drawn over the mastoid groove to intersect the first line. We have previously demonstrated that this point of intersection approximates the junction of transverse and sigmoid dural sinuses[3] and should therefore be designated as the summit of the curvilinear incision [Figure 3]. …”
Section: An Alternative Approach: the Curvilinear Incisionmentioning
confidence: 99%